Catechol‐O‐Methyltransferase Genotype Modulates Opioid Release in Decision Circuitry. Issue 5 (13th June 2013) - Mitchell, Jennifer M.; O'Neil, James P.; Jagust, William J.; Fields, Howard L.
Abstract: Impulsivity, a risk factor for substance abuse disorders, is modulated by the Val158 variant of the catechol‐O‐methyltransferase (COMT) gene. Rodent studies have shown that opioids enhance impulsivity. Furthermore, alcohol consumption leads to endogenous opioid release in the cortex and nucleus accumbens (NAc), and this opioid release is correlated with greater positive hedonic effect. Using the selective mu opioid receptor radioligand [ 11 C] carfentanil, we find that, following alcohol consumption, individuals with the COMT Val158 allele have greater opioid release in the right NAc but less release in medial orbital frontal cortex (OFC). These data suggest that genetic regulation of dopamine levels can affect alcohol consumption in part by modulating endogenous opioid release in specific brain regions implicated in reward, which in turn promotes impulsive choice.